High Frequency Buffer-Feedback Oscillator With an RF Negative-Resistance Circuit - Kang-Un Choi; Thanh Dat Nguyen; Seong-Gon Choi; Jong-Phil Hong (IEEE Access, 2018)
This paper presents a millimeter-wave oscillator using frequency-boosting techniques to increase the oscillation frequency. In the proposed oscillator, a buffer-feedback oscillator and an RF negative-resistance circuit reduce the parasitic load capacitance and effective inductance, respectively. As a result, the proposed topology operates at a higher oscillation frequency than the conventional oscillators. The proposed oscillator is fabricated in a 65-nm CMOS process. The measured oscillation frequency is 82.4 GHz, and the output power is -3.9 dBm. The power consumption is 10.9 mW at a supply voltage of 1.8 V, excluding output buffers.